ANALISIS PENGGUNAAN IRON SLAG SEBAGAI SUBSTITUSI AGREGAT HALUS TERHADAP KUAT TEKAN BETON - Ar-Rasyid, Arfan; Yakup, Vanita Kesumawati; Pratiwi, Dian (Universitas Teknokrat Indonesia, 2024)
Concrete construction is commonly used in tall buildings, bridges and other infrastructure. Therefore, innovation is needed in concrete formulations to improve concrete quality and reduce the negative impact of industrial construction on the environment. Iron slag, which is a waste produced during the smelting process of iron smelting, is one source of industrial waste that is attractive for use as a substitute for making concrete. The use of iron slag can reduce the amount of industrial waste and can also improve the mechanical properties of concrete. This research will study the potential for using iron slag (iron slag) as a substitute for fine aggregate in concrete. By looking at previous research in this area, as well as by understanding the basic properties of iron slag (iron slag) and the idea of its compressive strength, this research will investigate the possibility of using iron slag (iron slag) as a substitute for fine aggregate in concrete. In this research, variations in the iron slag used in the concrete mixture could not affect the increase in the compressive strength of the concrete. The compressive strength value of concrete experienced an optimum increase when the iron slag varied by 20% with a value of 21.35 Mpa. The value of the 20% variation is the variation with the highest compressive strength value compared to the 40%, 60% iron slag variation. but a variation of 20% does not exceed the design compressive strength and the value is below the normal concrete design compressive strength value of 24.9 Mpa